PI3Kγ Regulatory Protein p84 Determines Mast Cell Sensitivity to Ras Inhibition—Moving Towards Cell Specific PI3K Targeting? - Jin, Julie R.; Gogvadze, Elena; Xavier, Ana R.; Bohnacker, Thomas; Voelzmann, Jan; Wymann, Matthias P. (Frontiers in Immunology, 2020)
Mast cells are major effector cells in immunoglobulin E (IgE)-mediated allergy. The high affinity IgE receptor FceRI, as well as G protein-coupled receptors (GPCRs) on the mast cell surface signal to phosphoinositide 3-kinase gamma (PI3Kgamma) to initiate degranulation, cytokine release and chemotaxis. PI3Kgamma is therefore considered as a target for treatment of allergic disorders. However, leukocyte PI3Kgamma is key to many functions in innate and adaptive immunity, and attenuation of host defense mechanisms is an expected adverse effect that complicates treatment of chronic illnesses. PI3Kgamma operates as a p110gamma/p84 or p110gamma/p101 complex, where p110gamma/p84 requires Ras activation. Here we investigated if modulation of Ras-isoprenylation could target PI3Kgamma activity to attenuate PI3Kgamma-dependent mast cell responses without impairment of macrophage functions. In murine bone marrow-derived mast cells, GPCR stimulation triggers activation of N-Ras and H-Ras isoforms, which is followed by the phosphorylation of protein kinase B (PKB/Akt) relayed through PI3Kgamma. Although K-Ras is normally not activated in Ras wild-type cells, it is able to compensate for genetically deleted N- and H-Ras isoforms. Inhibition of Ras isoprenylation with farnesyltransferase inhibitor FTI-277 leads to a significant reduction of mast cell degranulation, cytokine production and migration. Complementation experiments expressing PI3Kgamma adaptor proteins p84 or p101 demonstrated a differential sensitivity towards Ras-inhibition depending on PI3Kgamma complex composition. Mast cell responses are exclusively p84-dependent, and were effectively controlled by FTI-277. Similar results were obtained when GTP-Ras was inactivated by overexpression of the GAP-domain of Neurofibromin-1 (NF-1). Unlike mast cells, macrophages express p84 and p101, but are p101-dominated and thus remain functional under treatment with FTI-277. Our work demonstrates that p101 and p84 have distinct physiological roles and that Ras dependence of PI3Kgamma signaling differs between cell types. FTI-277 reduces GPCR-activated PI3Kgamma responses in p84-expressing but not p101-containing bone marrow derived cells. However, prenylation inhibitors have pleiotropic effects beyond Ras and non-tolerable side-effects that disfavor further clinical validation. Statins are, however, clinically well-established drugs that have previously been proposed to block mast cell degranulation by interference with protein prenylation. We show here that Simvastatin inhibits mast cell degranulation, but that this does not occur via Ras-PI3Kgamma pathway alterations.